2017
DOI: 10.18332/ejm/76820
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ contribution to normal childbirth care. Cross-sectional study in public health Settings. MidconBirth Study protocol

Abstract: European Journal of Midwifery of low risk women in spontaneous labour 4 . It has been demonstrated that many common obstetric practices such as rupture of membranes for induction of labour, routine intrapartum amniotomy, continuous electronic foetal heart-rate monitoring or routine continuous infusion of intravenous fluids and oxytocin augmentation, are of limited benefit [5][6] . The range of and variation in the use of interventions in healthy low-risk women who are cared for in highly-technological birth en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Many studies have shown EA use during labor causes prolonged second stage (Rognant et al, 2012;.Borello-France et al, 2006,), which usually culminates in an instrumental birth with an episiotomy on many occasions [a risk factor of SPL on its own (Carolli et al, 2014;Escuriet et al, 2017]). Therefore, EA contributes to the causal chain of events leading to SPL (Lothian J., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown EA use during labor causes prolonged second stage (Rognant et al, 2012;.Borello-France et al, 2006,), which usually culminates in an instrumental birth with an episiotomy on many occasions [a risk factor of SPL on its own (Carolli et al, 2014;Escuriet et al, 2017]). Therefore, EA contributes to the causal chain of events leading to SPL (Lothian J., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a multicentre prospective study of women giving birth a live infant in 30 maternity hospitals in Catalonia from July 2016 and July 2017. Data for this study were obtained from MBC study database (Escuriet, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of maternity units also vary as does the degree of midwifery autonomy [ 6 ]. The most common model in European countries is that of providing care in conventional obstetrics units [ 9 ]. This translates into a situation in which most healthy women receive care in highly technological settings.…”
Section: Introductionmentioning
confidence: 99%